Innovative Learning Strategies: The Influence of Inquiry Learning and Reciprocal Teaching on Students’ Critical Thinking Skills in Mathematics Learning - Hadi, Heri Sopian; Farwati, Wiwik Wida; Irhas, Irhas (Universitas Nusantara PGRI Kediri, 2026)
This research is motivated by the importance of students' critical thinking skills in mathematics learning in the 21st century, which requires students not only to understand concepts but also to be able to analyze and solve problems logically. However, teacher-centered learning results in low student engagement and underdevelopment of critical thinking skills. Therefore, innovative learning strategies are needed that encourage activeness and higher-order thinking processes. Inquiry Learning and Reciprocal Teaching are two potential approaches, where Inquiry Learning emphasizes the process of discovery through investigation, while Reciprocal Teaching develops interaction and understanding through activities of summarizing, asking questions, and clarifying. The integration of these two strategies is expected to create more active and meaningful learning and improve students' critical thinking skills. Therefore, this study aims to analyze the influence of these two approaches in mathematics learning. The research employed a quasi-experimental approach using The Matching Only Post-test Only Group Design. The population consisted of eighth-grade students of MTs Nurul Jannah NW Ampenan. Class VIII A (20 students) was assigned to the Inquiry Learning group, while Class VIII B (16 students) received Reciprocal Teaching. Data were collected using an essay-type critical thinking test validated by experts. Analysis techniques included normality test, homogeneity test, and t-test at a 5% significance level. The findings reveal that both strategies significantly influence students’ critical thinking skills. Additionally, Inquiry Learning demonstrates a greater effect compared to Reciprocal Teaching, as indicated by higher mean scores and significant t-test results. The study highlights the importance of implementing innovative learning strategies to enhance students' critical thinking skills in mathematics.